1997
DOI: 10.1073/pnas.94.22.11839
|View full text |Cite
|
Sign up to set email alerts
|

The amino-terminal region of Tyk2 sustains the level of interferon α receptor 1, a component of the interferon α/β receptor

Abstract: Tyk2 belongs to the Janus kinase (JAK) family of receptor associated tyrosine kinases, characterized by a large N-terminal region, a kinase-like domain and a tyrosine kinase domain. It was previously shown that Tyk2 contributes to interferon-␣ (IFN-␣) signaling not only catalytically, but also as an essential intracellular component of the receptor complex, being required for high affinity binding of IFN-␣. For this function the tyrosine kinase domain was found to be dispensable. Here, it is shown that mutant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
117
0
1

Year Published

1998
1998
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 120 publications
(126 citation statements)
references
References 40 publications
6
117
0
1
Order By: Relevance
“…Therefore, it is critical to define the domains in Jaks and cytokine receptors responsible for this interaction to mimic or abrogate the activation of cytokine systems with specific drugs. Some reports have indicated that the N-terminal region, containing the JH7-6 domains, of Jak2, Jak3, and Tyk2 is critical for the association with receptors (42)(43)(44)(45)(46)(47)(48)(49). Our data (Fig.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Therefore, it is critical to define the domains in Jaks and cytokine receptors responsible for this interaction to mimic or abrogate the activation of cytokine systems with specific drugs. Some reports have indicated that the N-terminal region, containing the JH7-6 domains, of Jak2, Jak3, and Tyk2 is critical for the association with receptors (42)(43)(44)(45)(46)(47)(48)(49). Our data (Fig.…”
Section: Discussionsupporting
confidence: 56%
“…The JH7-6 domains of Tyk2 interact with IFN-␣R. Although a direct interaction between the JH5-4-3 domains of Tyk2 and IFN-␣R␣ has not been established, these domains are also required for kinase activation by the receptor (47)(48)(49).…”
mentioning
confidence: 99%
“…Second, the JH 6 -JH 7 domains of Tyk2 are also required for the interaction with the cytoplasmic portion of the IFNAR1 subunit ( Figure 8B). Interestingly, the JH 6 -JH 7 domains are required for e cient phosphorylation of IFNAR1 in vitro and for rendering the kinase activable by IFN-a (Gauzzi et al, 1997). Third, tyrosine phosphorylation of Tyk2 is diminished in cells expressing HPV-18 E6 after stimulation with IFN-a ( Figure 5A).…”
Section: Discussionmentioning
confidence: 99%
“…To this end, we used wt Tyk2 and E6 proteins bearing the vesicular stomatitis virus glycoprotein (VSV-G) (Gauzzi et al, 1997) and FLAG epitope in their C-terminus end respectively. VSV-GTyk2 and FLAG-E6 proteins were co-transfected in HeLa cells using the vaccinia virus/T7 system and their expression levels were detected by immunoblotting with either anti-VSV-G (Figure 7, top row) or anti-FLAG antibodies (second from the top row).…”
Section: Co-immunoprecipitation Of Tyk2 and E6 Proteinsmentioning
confidence: 99%
“…Considering the variety of interactions and functions performed by the JAK kinase family members it seemed plausible that these domains may be responsible for some key interactions with other proteins, which could act as their substrates. Recent studies indicate that the amino terminal regions are also involved in receptor binding (Gauzzi et al, 1997;Chen et al, 1997).…”
Section: Stat Signaling Pathwaysmentioning
confidence: 99%